REORIENTASI METODOLOGI PEMBELAJARAN TAFSIR DI MADRASAH DAN PESANTREN - Ainal Mardhiah (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2013)
One of the important subjects to be taught in Islamic Junior, Senior High and boarding school is Tafsir al-Qur'an (Quranic Interpretation) where in which could be implemented tahfiz (memorization of the verses) Tafsir, and Tarjamah (Quranic translation) and asbab al-nuzul (circumstance of the revelation) and munasabah (the verses congruity). In this paper the writer discusses a variety of learning methods in order to be implemented in Islamic school and Islamic boarding school. It is important as one of the effectiveness on the learning is influenced by the methods being used. The use of the method should be suit with each of the teaching material goal.